Fall Prevention in Community Settings: Results from Implementing Stepping On in Three States - Marcia Gail Ory; Matthew Lee eSmith; Luohua eJiang; Robin eLee; Shuai eChen; Ashley D Wilson; Judy A Stevens; Erin M Parker (Frontiers Media S.A., 2015)
.